S-Nitroso-L-Cysteine Ameliorated Pulmonary Hypertension in the MCT-Induced Rats through Anti-ROS and Anti-Inflammatory Pathways. (28th January 2021) - Wang, Moran; Luo, Pengcheng; Shi, Wei; Guo, Junyi; Huo, Shengqi; Yan, Dan; Peng, Lulu; Zhang, Cuntai; Lv, Jiagao; Lin, Li; Li, Sheng
Abstract : Pulmonary hypertension (PH) is a progressive and life-threatening chronic disease in which increased pulmonary artery pressure (PAP) and pulmonary vasculature remodeling are prevalent. Inhaled nitric oxide (NO) has been used in newborns to decrease PAP in the clinic; however, the effects of NO endogenous derivatives, S-nitrosothiols (SNO), on PH are still unknown. We have reported that S-nitroso-L-cysteine (CSNO), one of the endogenous derivatives of NO, inhibited RhoA activity through oxidative nitrosation of its C16/20 residues, which may be beneficial for both vasodilation and remodeling. In this study, we presented data to show that inhaled CSNO attenuated PAP in the monocrotaline- (MCT-) induced PH rats and, moreover, improved right ventricular (RV) hypertrophy and fibrosis induced by RV overloaded pressure. In addition, aerosolized CSNO significantly inhibited the hyperactivation of signal transducers and activators of transduction 3 (STAT3) and extracellular regulated protein kinases (ERK) pathways in the lung of MCT-induced rats. CSNO also regulated the expression of smooth muscle contractile protein and improved aberrant endoplasmic reticulum (ER) stress and mitophagy in lung tissues following MCT induction. On the other hand, CSNO inhibited reactive oxygen species (ROS) production in vitro, which is induced by angiotensin II (AngII) as well as interleukin 6 (IL-6). In addition, CSNO inhibited excessive ER stress and mitophagy induced by AngII and IL-6 in vitro; finally, STAT3 and ERK phosphorylation was inhibited by CSNO in a concentration-dependent manner. Taken together, CSNO led to pulmonary artery relaxation and regulated pulmonary circulation remodeling through anti-ROS and anti-inflammatory pathways and may be used as a therapeutic option for PH treatment.